Sosialisasi dan Pelatihan Penggunaan Aplikasi “BukuWarung” sebagai Alat Pembukuan Keuangan Sederhana Bagi Pelaku UMKM di Kelurahan Tenggilis Mejoyo Surabaya - Dinda Eka Rahmawati; Ratih Mukti Azhar (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The research in this journal has explained that MSMEs in Tenggilis Mejoyo Village face traditional bookkeeping challenges that are prone to errors. To overcome this, socialisation activities and training on the use of the "BukuWarung" application were carried out. The purpose of the service is to increase MSME understanding of the application. The results of the service showed that MSMEs still did not understand the importance of bookkeeping. The "BukuWarung" application was explained as an efficient modern solution. MSME players were given training and practice using the application, with the advantages of being free, clear recording of transactions, and monitoring of stock items. Nevertheless, the application has shortcomings related to data security and some user complaints. Overall, the service activities made a positive contribution in increasing MSMEs' understanding and acceptance of the "BukuWarung" application. Hopefully, the use of this technology can support the growth of MSMEs in the region.